Insights into IL-1 family cytokines in kidney allograft transplantation: IL-18BP and free IL-18 as emerging biomarkers - Cecrdlova, E.; Krupickova, L.; Fialova, M.; Novotny, M.; Tichanek, F.; Svachova, V.; Mezerova, K.; Viklicky, O.; Striz, I. (Cytokine (Philadelphia, Pa.), 2024)
[Display omitted] •Serum levels of the proinflammatory IL-1beta, IL-18, and IL-36beta are downregulated after kidney transplantation.•Concentrations of calculated free IL-18 and IL-18BP are increased at the time of acute rejection.•Serum IL-18BP concentrations may be partially affected by kidney functions. Proinflammatory cytokines and their inhibitors are involved in the regulation of multiple immune reactions including response to transplanted organs. In this prospective study, we evaluated changes in serum concentrations of six IL-1 family cytokines (IL-1 alpha, IL-1 beta, IL-1RA, IL-18, IL-18BP, and IL-36 beta) in 138 kidney allograft recipients and 48 healthy donors. Samples were collected before transplantation and then after one week, three months and one year, additional sera were obtained at the day of biopsy positive for acute rejection. We have shown, that concentrations of proinflammatory members of the IL-1 family (IL-1β, IL-18, IL-36 β) and anti-inflammatory IL-18BP decreased immediately after the transplantation. The decline of serum IL-1RA and IL-1α was not observed in subjects with acute rejection. IL-18, including specifically its free form, is the only cytokine which increase serum concentrations in the period between one week and three months in both groups of patients without upregulation of its inhibitor, IL-18BP. Serum concentrations of calculated free IL-18 were upregulated in the acute rejection group at the time of acute rejection. We conclude that IL-1 family cytokines are involved mainly in early phases of the response to kidney allograft. Serum concentrations of free IL-18 and IL-18BP represent possible biomarkers of acute rejection, and targeting IL-18 might be of therapeutic value.